Negative electrode binder composition, negative electrode binder, preparation method of negative electrode binder, negative electrode plate, battery cell and battery

By using acrylic monomers, hydroxydopamine monomers, long-chain alkyl (meth)acrylate monomers and vinylsiloxane monomers, the problem of insufficient adhesion of traditional adhesives at high temperatures is solved, and higher adhesion, chemical stability and high and low temperature resistance are achieved, and the cycle life of lithium-ion batteries is extended.

CN119752367AActive Publication Date: 2025-04-04BYD CO LTD

Patent Information

Application Number
CN202410866953.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-28
Publication Date
2025-04-04
Estimated Expiration
2044-06-28

AI Technical Summary

Technical Problem

When traditional SBR and PAA negative electrode binders are used in high temperature environments, their bonding strength is insufficient and they are prone to aging and becoming brittle, resulting in the rupture and powderization of the negative electrode material, and reducing the cycle life of the lithium-ion battery.

Method used

A negative electrode binder composition, including acrylic monomers, hydroxydopamine monomers, long-chain alkyl (meth)acrylate monomers and vinyl siloxane monomers, is used to prepare a negative electrode binder with excellent bonding strength, chemical stability and high and low temperature resistance through specific chemical reaction steps.

Benefits of technology

It significantly enhances the adhesion of the negative electrode adhesive to the current collector, improves chemical stability and high and low temperature resistance, and extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The embodiment of the invention discloses a negative electrode binder composition, a negative electrode binder, a preparation method of the negative electrode binder, a negative electrode plate, a battery cell and a battery. Wherein the negative electrode binder composition comprises the following components: an acrylic acid monomer, a hydroxydopamine monomer, a long-chain alkyl (methyl) acrylate monomer and a vinyl siloxane monomer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of battery technology. Specifically, the present application relates to a negative electrode binder composition, a negative electrode binder and a preparation method thereof, a negative electrode sheet, a battery cell and a battery. Background Art

[0002] With the rapid development of electronic technology, lithium-ion batteries have been widely used in fields such as electric vehicles and smart phones due to their advantages such as high energy density, long life and environmental protection.

[0003] However, when the battery is operated at a higher temperature, the traditional SBR (styrene butadiene rubber emulsion) and PAA (polyacrylic acid) negative electrode binders have insufficient bonding strength in the electrolyte and are prone to aging and brittleness, which can cause the negative electrode material to break and powderize, and then fall off from the current collector (such as copper sheet), seriously reducing the cycle life of the battery. Therefore, the development of negative electrode binders with strong bonding strength and stability in the electrolyte is of great significance to improve the cycle life of lithium-ion batteries. Summary of the invention

[0004] The purpose of the present application is to provide a new technical solution for a negative electrode binder composition, a negative electrode binder and a preparation method thereof, a negative electrode sheet, a battery cell and a battery.

[0005] According to the first aspect of the present application, an embodiment of the present application provides a negative electrode binder composition, wherein the negative electrode binder composition comprises the following components:

[0006] Acrylic monomers, hydroxydopamine monomers, long-chain alkyl (meth)acrylate monomers and vinyl siloxane monomers.

[0007] Optionally, the mass fractions of the acrylic monomer, the hydroxydopamine monomer, the long-chain alkyl (meth)acrylate monomer and the vinyl siloxane monomer are as follows:

[0008] The acrylic monomer is 50 to 100 parts;

[0009] The hydroxydopamine monomer is 90 to 180 parts;

[0010] The long-chain alkyl (meth) acrylate monomer is 20 to 40 parts;

[0011] The vinyl siloxane monomer is 30 to 60 parts.

[0012] Optionally, the negative electrode binder composition further comprises an initiator and a surfactant;

[0013] The amount of the initiator is 0.1 wt% to 1 wt% of the total mass of the acrylic monomer, the hydroxydopamine monomer, the long-chain alkyl (meth) acrylate monomer and the vinyl siloxane monomer; and / or,

[0014] The amount of the surfactant used is 0.5 wt % to 1 wt % of the total weight of the acrylic monomer, the hydroxydopamine monomer, the long-chain alkyl (meth)acrylate monomer and the vinyl siloxane monomer.

[0015] Optionally, the acrylic monomer includes at least one of acrylic acid and methacrylic acid;

[0016] The long-chain alkyl (meth)acrylate monomer includes at least one of lauryl methacrylate, myristyl methacrylate, stearic methacrylate and 2-ethylhexyl acrylate.

[0017] Optionally, the vinyl siloxane monomer includes at least one of vinyl trimethoxy silane, vinyl triethoxy silane, vinyl triisopropoxy silane and γ-methacryloxypropyl trimethoxy silane.

[0018] Optionally, the initiator includes at least one of potassium persulfate, ammonium persulfate and sodium persulfate.

[0019] Optionally, the surfactant includes at least one of sodium dodecyl sulfate, sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, sodium dioctyl sulfosuccinate, polyoxyethylene nonylphenol ether and polyoxyethylene octylphenol ether.

[0020] According to the second aspect of the present application, an embodiment of the present application provides a negative electrode binder, and the chemical structural formula of the negative electrode binder is as follows:

[0021]

[0022] In the formula: x, y, z represent quantity, x, y, z are positive integers, and the ratio of x, y, z is 5~10:1~2:2~4.

[0023] According to the third aspect of the present application, an embodiment of the present application provides a method for preparing a negative electrode binder, comprising:

[0024] The acrylic monomer and the hydroxydopamine monomer are mixed and reacted to obtain a reactant;

[0025] A long-chain alkyl (meth) acrylate monomer and a vinyl siloxane monomer are added to the reactant, and then a polymerization reaction is carried out in the presence of a surfactant and an initiator to prepare a negative electrode binder.

[0026] Optionally, the mass ratio of the hydroxydopamine monomer to the vinylsiloxane monomer is 1.5 to 6:1.

[0027] Optionally, the acrylic acid monomer and the hydroxydopamine monomer are mixed and reacted to obtain a reactant comprising:

[0028] The acrylic monomer and the hydroxydopamine monomer are mixed and reacted at 50° C. to 70° C. for 1 h to 2 h.

[0029] Optionally, the adding of a long-chain alkyl (meth) acrylate monomer and a vinyl siloxane monomer to the reactant, and then performing a polymerization reaction in the presence of a surfactant and an initiator to obtain a negative electrode binder comprises:

[0030] Adding the long-chain alkyl (meth) acrylate monomer and the surfactant to the reactant obtained after the acrylic monomer and the hydroxydopamine monomer are mixed and reacted, and adding deionized water to prepare a pre-emulsion;

[0031] Add the initiator to the pre-emulsion, introduce nitrogen as a protective gas, raise the temperature to 75°C to 85°C and then keep it warm, then add the vinyl siloxane monomer and continue to keep it warm at 75°C to 85°C to obtain an emulsion; wherein the total time of the second heat preservation is 1 to 3 hours;

[0032] The emulsion is filtered and dried to obtain the negative electrode binder.

[0033] According to a fourth aspect of the present application, an embodiment of the present application provides a negative electrode sheet, the negative electrode sheet comprising a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, the negative electrode active material layer comprising a negative electrode active material and a conductive agent; the negative electrode active material layer is bonded to the negative electrode current collector by a binder;

[0034] Wherein, the binder is the negative electrode binder composition as described in the first aspect or the negative electrode binder as described in the second aspect.

[0035] According to a fifth aspect of the present application, an embodiment of the present application provides a battery cell, the battery cell comprising: a positive electrode sheet, a negative electrode sheet and a separator;

[0036] Wherein, the negative electrode sheet is the negative electrode sheet as described in the fourth aspect.

[0037] According to the sixth aspect of the present application, an embodiment of the present application provides a battery, comprising a housing, a battery cell and an electrolyte; wherein the battery cell is the battery cell as described in the fifth aspect.

[0038] One beneficial effect of the embodiments of the present application is:

[0039] According to the negative electrode binder composition proposed in the embodiment of the present application, its components include at least four monomers. Specifically, by using hydroxydopamine and vinyl siloxane monomers to modify the copolymer synthesized from acrylic acid and long-chain alkyl (meth) acrylate monomers, a negative electrode binder with excellent bonding force, chemical stability and high and low temperature resistance can be prepared; wherein, the ortho-diphenol hydroxyl group in hydroxydopamine can form a strong hydrogen bond, and this characteristic greatly enhances the adhesion of the obtained negative electrode binder to the current collector. By introducing vinyl siloxane monomers for modification, the chemical stability of the negative electrode binder has been significantly improved, and the strength of the Si-O bond is significantly higher than that of the CC bond and the CO bond, which makes the modified binder show higher stability when facing chemical environments such as electrolytes. In addition, since three alkoxy groups are connected to the silicon atom connected to the carbon atom, this structure makes the molecular chain more stable and not easy to rotate, thereby further enhancing the chemical stability and structural strength of the formed negative electrode binder.

[0040] Other features and advantages of the present application will become apparent from the following detailed description of exemplary embodiments of the present application. DETAILED DESCRIPTION

[0041] Various exemplary embodiments of the present application are now described in detail. It should be noted that the relative arrangement of components and steps, numerical expressions and numerical values ​​set forth in these embodiments do not limit the scope of the present application unless otherwise specifically stated.

[0042] The following description of at least one exemplary embodiment is merely illustrative in nature and is in no way intended to limit the present application, its application, or uses.

[0043] Techniques and equipment known to ordinary technicians in the relevant art may not be discussed in detail, but where appropriate, the techniques and equipment should be considered part of the specification.

[0044] In all examples shown and discussed herein, any specific values ​​should be interpreted as merely exemplary and not limiting. Therefore, other examples of the exemplary embodiments may have different values.

[0045] The negative electrode binder composition, negative electrode binder and preparation method thereof, negative electrode sheet, battery cell and battery provided in the embodiments of the present application are described in detail below.

[0046] According to one embodiment of the present application, a negative electrode binder composition is provided, wherein the negative electrode binder composition comprises the following components:

[0047] Acrylic monomers, hydroxydopamine monomers, long-chain alkyl (meth)acrylate monomers and vinyl siloxane monomers.

[0048] According to the negative electrode binder composition provided in the embodiment of the present application, it mainly involves different monomers, namely the above-mentioned four monomers: acrylic monomer, hydroxydopamine monomer, long-chain alkyl (meth) acrylate monomer and vinyl siloxane monomer. The above-mentioned four monomers are prepared into a negative electrode binder with specific properties through specific chemical reaction steps.

[0049] Specifically, the process of obtaining the negative electrode binder includes the following key steps:

[0050] In the first step, acrylic monomers and hydroxydopamine monomers are mixed and reacted. Acrylic monomers (such as acrylic acid, methacrylic acid, etc.) are mixed and reacted with hydroxydopamine monomers. The purpose of this step is to use the ortho-diphenolic hydroxyl groups in hydroxydopamine to replace the carboxyl hydroxyl groups in the binder, thereby helping to enhance the adhesion of the binder to the current collector.

[0051] In the second step, long-chain alkyl (meth) acrylate monomers and vinyl siloxane monomers are added. On the basis of the first step reaction, the addition of long-chain alkyl (meth) acrylate monomers and vinyl siloxane monomers is intended to further improve the chemical stability, aging resistance, high and low temperature resistance and solvent resistance of the formed negative electrode binder.

[0052] The third step is polymerization reaction. For example, the product obtained in the second step can be subjected to polymerization reaction in the presence of a surfactant and an initiator. The purpose of this step is to allow various monomers to fully react, thereby forming a negative electrode binder with a specific structure and performance.

[0053] According to the negative electrode binder provided in the embodiment of the present application, the hydroxydopamine used therein exhibits excellent adhesion due to its unique ortho-diphenolic hydroxyl structure, and this adhesion comes from its ability to form strong hydrogen bonds. In the preparation process of the negative electrode binder, the ortho-diphenolic hydroxyl group of hydroxydopamine is used to replace the original carboxyl hydroxyl group, which not only significantly enhances the adhesion ability of the negative electrode binder to the current collector, but also further improves the stability and reliability of the battery. In other words, due to the introduction of hydroxydopamine, the adhesion of the final formed negative electrode binder to, for example, the negative electrode current collector can be significantly enhanced, which helps to prevent the problem of the negative electrode material falling off during the charging and discharging process.

[0054] Furthermore, the chemical stability of the negative electrode binder is improved by introducing vinyl siloxane monomers for organosilicon modification. This is because the strength of the Si-O bond is significantly higher than that of the traditional CC bond and CO bond, which makes the obtained negative electrode binder show higher stability when facing complex chemical environments such as electrolytes. It is worth mentioning that three alkoxy groups are connected to the silicon atom connected to the carbon atom. This structure makes the molecular chain more stable and less prone to rotation, thereby further enhancing the tensile strength and structural strength of the negative electrode binder. At the same time, this organosilicon modification also gives the negative electrode binder excellent aging resistance, high and low temperature resistance, and solvent resistance. In extreme working environments, it can still maintain stable performance, especially the durability to the electrolyte under high temperature conditions is particularly remarkable.

[0055] Therefore, the negative electrode sheet prepared using the negative electrode binder provided in the embodiments of the present application can exhibit higher cycle life, lower internal resistance and better rate performance in, for example, lithium-ion batteries, thereby improving the overall performance of the battery.

[0056] The negative electrode binder solution provided in the embodiment of the present application is very different from the traditional polyacrylic acid PAA that relies solely on the synthesis of acrylic acid and its esters. The technical solution provided in this application uses hydroxydopamine monomers and vinylsiloxane monomers to modify acrylic acid and its long-chain esters, thereby giving the final negative electrode binder new properties and characteristics. This method not only breaks the traditional constraints, but also achieves significant improvements in the adhesion, chemical stability, aging resistance, high and low temperature resistance, and solvent resistance of the negative electrode binder, opening up a new path for the optimization of negative electrode materials and the improvement of battery performance.

[0057] According to the negative electrode binder composition provided by the embodiment of the present application, its components include at least four monomers. Specifically, by using hydroxydopamine and vinyl siloxane monomers to modify the copolymer synthesized from acrylic monomers and long-chain alkyl (meth) acrylate monomers, a negative electrode binder with excellent bonding force, chemical stability and high and low temperature resistance can be prepared; wherein, the ortho-diphenol hydroxyl group in hydroxydopamine can form a strong hydrogen bond, and this characteristic greatly enhances the adhesion of the obtained negative electrode binder to the current collector. By introducing vinyl siloxane monomers for modification, the negative electrode binder has been significantly improved in chemical stability, and the strength of the Si-O bond is significantly higher than that of the CC bond and the CO bond, which makes the modified binder show higher stability when facing chemical environments such as electrolytes. In addition, since three alkoxy groups are connected to the silicon atom connected to the carbon atom, this structure makes the molecular chain more stable and not easy to rotate, thereby further enhancing the chemical stability and structural strength of the formed negative electrode binder.

[0058] In some examples of the present application, the mass fractions of the acrylic monomer, the hydroxydopamine monomer, the long-chain alkyl (meth)acrylate monomer and the vinyl siloxane monomer are as follows: the acrylic monomer is 50 to 100 parts, the hydroxydopamine monomer is 90 to 180 parts, the long-chain alkyl (meth)acrylate monomer is 20 to 40 parts, and the vinyl siloxane monomer is 30 to 60 parts.

[0059] According to the examples of the present application, the mass fraction ranges of the acrylic monomer, the hydroxydopamine monomer, the long-chain alkyl (meth)acrylate monomer and the vinyl siloxane monomer in the raw materials of the negative electrode binder composition are described.

[0060] The mass fraction of acrylic monomer is 50 to 100 parts. Acrylic monomer is the basic raw material for preparing negative electrode binder, which provides the basic structure and performance of negative electrode binder. Within this dosage range, the amount of acrylic monomer is sufficient to ensure the basic performance of the binder, and there is also a certain adjustment space to adapt to different application requirements.

[0061] The mass fraction of hydroxydopamine monomer is 90 to 180 parts. As one of the modifiers, the introduction of a high content of hydroxydopamine monomer (relative to acrylic monomer) is to significantly enhance the adhesion of the final negative electrode binder. In the range of 90 to 180 parts, when combined with acrylic monomer, the adhesion of hydroxydopamine can be fully demonstrated, ensuring a firm connection between the negative electrode active material and the negative electrode current collector, while not causing other performance problems due to excessive content.

[0062] The mass fraction of the long-chain alkyl (meth) acrylate monomer is 20 to 40 parts. The addition of the long-chain alkyl (meth) acrylate monomer can improve the flexibility and processing performance of the final negative electrode binder, and also help to improve the compatibility of the negative electrode binder with the negative electrode active material and the negative electrode current collector. The content within this range can ensure the improvement of the above-mentioned properties without having a negative impact on the overall performance.

[0063] The mass fraction of vinyl siloxane monomers is 30 to 60 parts. The addition of vinyl siloxane monomers can significantly improve the chemical stability and aging resistance, high and low temperature resistance, and solvent resistance of the final negative electrode binder. The content within this range is combined with the content of other monomers to ensure the improvement of the above-mentioned properties, while not increasing costs or reducing other properties due to excessive content.

[0064] Based on the mass fractions of the above components, this component formula can prepare a negative electrode binder with excellent adhesion, chemical stability, aging resistance, high and low temperature resistance, and solvent resistance. This binder can not only ensure a firm connection between the negative electrode active material and the negative electrode current collector, but also improve the stability and reliability of the battery using the negative electrode sheet and extend the battery life.

[0065] It is further preferred that the mass fractions of the acrylic monomer, the hydroxydopamine monomer, the long-chain alkyl (meth)acrylate monomer and the vinyl siloxane monomer are as follows:

[0066] The acrylic monomer is 50 to 100 parts, the hydroxydopamine monomer is 90 to 120 parts, the long-chain alkyl (meth)acrylate monomer is 20 to 40 parts, and the vinyl siloxane monomer is 40 to 50 parts.

[0067] The mass fraction distribution of the above preferred solution provides a more accurate and efficient formula for the preparation of the negative electrode binder. Compared with the above examples of the present application, the amount of hydroxydopamine monomer and vinylsiloxane monomer is further optimized. Specifically:

[0068] The mass fraction of the hydroxydopamine monomer is preferably set to 90 to 120 parts. The addition optimization of the hydroxydopamine monomer can enhance the adhesion performance of the final negative electrode binder. Within this range, its content is sufficient to exert the strong adhesion effect of the ortho-diphenol hydroxyl group, and will not cause other performance degradation due to excessive amount, and can also reduce production costs.

[0069] The mass fraction of vinyl siloxane monomers is 40 to 50 parts. The addition optimization of vinyl siloxane monomers can improve the chemical stability, aging resistance, high and low temperature resistance and solvent resistance of the negative electrode binder. In particular, the mass fraction of vinyl siloxane monomers is controlled at 40 to 50 parts, so that the mass ratio of vinyl siloxane monomers to hydroxydopamine monomers is maintained in the preferred range of 1.8 to 3:1. This more preferred ratio allows the binder to maintain high adhesion while also having excellent stability and durability.

[0070] It should be noted that an increase in the mass fraction of the vinyl siloxane monomer, such as greater than 60 parts, or a decrease in the mass fraction of the vinyl siloxane monomer, such as less than 30 parts, will result in a decrease in the viscosity or peeling force of the formed negative electrode binder.

[0071] The optimization of the mass fraction range of each monomer provided in the example of this application can bring the following technical effects:

[0072] (1) Excellent adhesion: The optimized control of the amount of hydroxydopamine monomer ensures a strong connection between the prepared negative electrode binder and the negative electrode active material and the negative electrode current collector.

[0073] (2) Enhanced chemical stability: The addition of vinylsiloxane monomers significantly improves the chemical stability of the negative electrode binder, allowing it to remain stable in a complex chemical environment.

[0074] (3) Good aging resistance, high and low temperature resistance and solvent resistance: By optimizing the formula, the final negative electrode binder exhibits excellent aging resistance, high and low temperature resistance and solvent resistance, which helps to extend the service life of the battery.

[0075] (4) Balance of comprehensive performance: While maintaining high adhesion, this optimization scheme also focuses on the balance of other properties, such as chemical stability and aging resistance, providing strong support for the preparation of high-performance negative electrode binders.

[0076] In some examples of the present application, the negative electrode binder composition further includes an initiator, and the amount of the initiator is 0.1 wt % to 1 wt % of the total mass of the acrylic monomer, the hydroxydopamine monomer, the long-chain alkyl (meth)acrylate monomer and the vinyl siloxane monomer.

[0077] Initiators play a key role in starting or initiating the polymerization process in polymerization reactions, and their main function is to convert monomers into polymers. In the technical solution provided in the embodiments of the present application, the initiator plays a vital role in the polymerization reactions of the acrylic monomers, the hydroxydopamine monomers, the long-chain alkyl (meth) acrylate monomers, and the vinyl siloxane monomers.

[0078] (1) Initiation of polymerization: Initiators can be decomposed by heat into active intermediates such as free radicals, cations or anions, which can attack monomer molecules, thereby starting the polymerization process. In this application, an appropriate amount of initiator can ensure the smooth progress of the polymerization reaction and form a polymer chain.

[0079] (2) Controlling the polymerization reaction rate: The concentration and activity of the initiator directly affect the polymerization reaction rate. In the embodiment of the present application, by precisely controlling the amount of the initiator, i.e., 0.1 wt% to 1 wt%, the polymerization reaction rate can be regulated to meet the needs of different application scenarios.

[0080] (3) The selection and use of initiators not only affect the progress of the polymerization reaction, but also affect the performance of the final product. In this application, optimizing the amount of initiator is helpful to improve the adhesion, chemical stability and other properties of the negative electrode binder.

[0081] In some examples of the present application, the composition of the negative electrode binder also includes a surfactant, and the amount of the surfactant is 0.5wt% to 1wt% of the total mass of the acrylic monomer, the hydroxydopamine monomer, the long-chain alkyl (meth)acrylate monomer and the vinyl siloxane monomer.

[0082] In the example of this application, the role of the surfactant is as follows:

[0083] Surfactants can interact with the anode binder molecules to form stronger chemical bonds, which helps improve the adhesion and adhesion of the anode binder. This is particularly important in the preparation of anode binders because it ensures a strong connection between the anode material and the current collector.

[0084] Surfactants can improve emulsion stability. Binders often contain impurities such as fillers and additives, which can easily lead to stratification and precipitation. The role of surfactants is to disperse these impurities in the water phase to form a stable emulsion state, thereby ensuring the stability and service life of the binder.

[0085] The type and amount of surfactant can affect the fluidity, viscosity, drying time and other properties of the final prepared negative electrode binder. By adjusting the amount of surfactant, the negative electrode binding properties and functions can be customized to meet different application requirements.

[0086] In some examples of the present application, the acrylic monomer includes at least one of acrylic acid and methacrylic acid.

[0087] In some examples of the present application, the long-chain alkyl (meth)acrylate monomer includes at least one of lauryl methacrylate, myristyl methacrylate, stearic methacrylate, and 2-ethylhexyl acrylate.

[0088] In the above examples provided in the present application, specific types of acrylic monomers and long-chain alkyl (meth)acrylate monomers used are further described.

[0089] The acrylic monomers include, for example, at least one of acrylic acid and methacrylic acid, which are basic raw materials for preparing polymers and have good polymerization activity.

[0090] Among them, acrylic acid is an unsaturated carboxylic acid with two functional groups, a double bond and a carboxyl group, which can be copolymerized with a variety of monomers. Acrylic polymers have good adhesion, film-forming properties and water resistance.

[0091] Among them, methacrylic acid is a methyl derivative of acrylic acid, and its polymer has higher hardness and weather resistance than acrylic polymer.

[0092] It should be noted that, in addition to the above-mentioned acrylic acid or methacrylic acid, the acrylic acid monomer may also be acrylic acid of other bases, which is not limited in the present application.

[0093] The long-chain alkyl (meth) acrylate monomer includes at least one of lauryl methacrylate, myristyl methacrylate, stearic methacrylate and 2-ethylhexyl acrylate. These monomers contain long-chain alkyl groups and can provide excellent hydrophobicity, softness and lubricity to the polymer.

[0094] Lauryl Methacrylate: Lauryl is a C12 long-chain alkyl group. The polymer of lauryl methacrylate has good softness and hydrophobicity.

[0095] Tetradecyl Methacrylate: It is a C14 long chain alkyl group. Its polymer has a longer alkyl chain than the polymer of lauryl methacrylate, so it has better hydrophobicity and softness.

[0096] Stearic methacrylate: stearyl is a C18 long-chain alkyl group. The polymer of stearic methacrylate has excellent hydrophobicity, softness and lubricity.

[0097] 2-Ethylhexyl Acrylate: This monomer combines the unsaturation of acrylic acid with the long-chain alkyl of 2-ethylhexyl, and its polymer has excellent flexibility and weather resistance.

[0098] The acrylic monomer provided according to the example of the present application is at least one of acrylic acid and methacrylic acid, which can make the prepared negative electrode binder have excellent adhesion and film-forming properties.

[0099] The long-chain alkyl (meth) acrylate monomer provided according to the example of the present application includes at least one of lauryl methacrylate, myristyl methacrylate, stearic methacrylate and 2-ethylhexyl acrylate. The introduction of the long-chain alkyl (meth) acrylate monomer provides the polymer with good softness and hydrophobicity, so that the polymer material has excellent water resistance and flexibility while maintaining a certain mechanical strength.

[0100] In some examples of the present application, the vinyl siloxane monomer includes at least one of vinyl trimethoxy silane, vinyl triethoxy silane, vinyl triisopropoxy silane and γ-methacryloxypropyl trimethoxy silane.

[0101] Monomers such as vinyl trimethoxysilane, vinyl triethoxysilane and vinyl triisopropoxysilane have excellent reactivity and cross-linking ability, and can effectively copolymerize with the acrylic monomers, the hydroxydopamine monomers and the long-chain alkyl (meth) acrylate monomers to form polymers with excellent properties. Such polymers not only have good adhesion and mechanical strength, but also have excellent weather resistance, chemical corrosion resistance and heat resistance.

[0102] γ-Methacryloxypropyltrimethoxysilane is a silane monomer with acryloxy reactivity. It can improve the mechanical properties of composite materials and improve the compatibility between inorganic fillers and polymers.

[0103] The various vinyl siloxane monomers mentioned above can copolymerize with other monomers to form polymers with excellent adhesion and mechanical strength, ensuring that the product can maintain stable performance during use.

[0104] The various vinyl siloxane monomers mentioned above impart good weather resistance and chemical corrosion resistance to the polymer, allowing the product to be used for a long time in harsh environments without being damaged.

[0105] The various vinylsiloxane monomers mentioned above can significantly improve the heat resistance and aging resistance of the final negative electrode binder.

[0106] Silane monomers with acryloxy reactivity, such as γ-methacryloxypropyltrimethoxysilane, can improve the compatibility between inorganic fillers and polymers and enhance the performance of composite materials.

[0107] In some examples of the present application, the initiator includes at least one of potassium persulfate, ammonium persulfate and sodium persulfate.

[0108] Initiator is a compound that can produce free radicals or ions in the polymerization reaction, thereby initiating the polymerization of monomers. The initiator involved in the examples of the present application includes one or more of potassium persulfate, ammonium persulfate and sodium persulfate. The above-mentioned initiators are all persulfate compounds, which can decompose and produce sulfuric acid free radicals under heat or light conditions, thereby initiating the polymerization of monomers. The above-mentioned initiators have high initiation efficiency and stability and can be used in a wide temperature and pH range. By selecting a suitable initiator and adjusting its dosage, the rate of the polymerization reaction and the molecular weight distribution of the polymer can be controlled, thereby obtaining a polymer with specific properties.

[0109] In polymerization reactions, initiators are usually used in small amounts, but they have an important influence on the polymerization process and the properties of the final product.

[0110] In some examples of the present application, the surfactant includes at least one of sodium dodecyl sulfate, sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, sodium dioctyl sulfosuccinate, polyoxyethylene nonylphenol ether, and polyoxyethylene octylphenol ether.

[0111] Surfactants are substances that can significantly reduce the surface tension of a solvent. The surfactants involved in the examples of this application include: one or more of sodium dodecyl sulfate, sodium dodecyl sulfonate, and sodium dodecylbenzene sulfonate.

[0112] Sodium dodecyl sulfate (SDS): It is a common anionic surfactant with good detergency and emulsification abilities.

[0113] Sodium dodecyl sulfate (also known as sodium lauryl sulfate): Different from SDS, but also an anionic surfactant.

[0114] Sodium dodecylbenzene sulfonate (SDBS): It is another anionic surfactant with good stability and biodegradability.

[0115] Sodium dioctyl sulfosuccinate: can be used as a co-solvent.

[0116] 4-Nonylphenol Polyoxyethylene ether and 4-Octylphenol Polyoxyethylene ether: These two are polyoxyethylene ether derivatives, used as non-ionic surfactants, and have good emulsifying, dispersing and solubilizing abilities.

[0117] The above-mentioned surfactants can be used as emulsifiers, dispersants, solubilizers, etc. in the polymerization reaction, which helps to improve the stability and uniformity of the polymerization system. In the final negative electrode binder, they can give the material specific surface properties, such as wettability, emulsification, dispersibility, etc., to meet different application requirements.

[0118] According to a second embodiment of the present application, a negative electrode binder is provided, and the chemical structural formula of the negative electrode binder is as follows:

[0119]

[0120] In the formula: x, y, z represent quantity, x, y, z are positive integers, and the ratio of x, y, z is 5-10:1-2:2-4.

[0121] According to the chemical structure of the negative electrode binder, it contains methyl (CH3), methylene (CH2-), carbonyl (CO, C=O), amino (NH), hydroxyl (OH) and siloxane group (Si—O—CH3). The negative electrode binder can be considered as acrylic acid and ester polymer modified by hydroxydopamine and siloxane.

[0122] In the chemical structure of the negative electrode binder, the siloxane group (Si—O—CH3) indicates that this is a siloxane-modified molecule. Siloxane modification can be used to improve the surface properties, stability or compatibility of the material with other materials. Acrylic acid and ester polymers are polymers with carbon-carbon double bonds (C=C) and carbonyl (C=O) structures.

[0123] Hydroxydopamine is a hydroxylated derivative of dopamine. From the chemical structure of the negative electrode binder, there are multiple hydroxyl groups (OH), which is one of the significant characteristics of hydroxydopamine.

[0124] In the negative electrode binder, hydroxydopamine interacts with siloxane-modified acrylic acid and ester polymers through its specific functional groups to enhance the adhesion and stability of the binder. Hydroxydopamine also has a certain electrochemical activity and can participate in the electrode reaction during the charge and discharge process, thereby improving the electrochemical performance of the negative electrode material.

[0125] The negative electrode binder provided in the embodiment of the present application is prepared by using the above-mentioned negative electrode binder composition, which has excellent adhesion and stability, and can effectively bond the negative electrode active material with the current collector and other components to prevent the active material from falling off and pulverizing during the charging and discharging process. This material design helps to improve the overall performance of the battery, such as cycle life, energy density and safety. At the same time, its excellent adhesion and stability also help to improve the reliability and durability of the battery.

[0126] According to a third embodiment of the present application, a method for preparing a negative electrode binder is provided, wherein the negative electrode binder is the negative electrode binder described above.

[0127] The method for preparing the negative electrode binder provided in the embodiment of the present application comprises the following steps 1 and 2:

[0128] Step 1, mixing an acrylic monomer and a hydroxydopamine monomer and reacting them to obtain a reactant;

[0129] Step 2: adding a long-chain alkyl (meth) acrylate monomer and a vinyl siloxane monomer to the reactant, and then performing a polymerization reaction in the presence of a surfactant and an initiator to obtain a negative electrode binder.

[0130] The prepared negative electrode binder is hydroxydopamine and siloxane-modified acrylic acid and ester polymer, and the chemical structural formula of the negative electrode binder is as follows:

[0131]

[0132] In the formula: x, y, z represent quantity, x, y, z are positive integers, and the ratio of x, y, z is 5-10:1-2:2-4.

[0133] According to the preparation method of the negative electrode binder proposed in the embodiment of the present application, a copolymer synthesized from acrylic acid and long-chain alkyl (meth) acrylate monomers is modified by using hydroxydopamine and vinyl siloxane monomers to prepare a negative electrode binder with excellent bonding force, chemical stability and high and low temperature resistance; wherein, the ortho-diphenolic hydroxyl group in hydroxydopamine can form a strong hydrogen bond, and this characteristic greatly enhances the adhesion of the formed negative electrode binder to the current collector, and by introducing vinyl siloxane monomers for modification, the negative electrode binder has been significantly improved in chemical stability, and the strength of the Si-O bond is significantly higher than that of the CC bond and the CO bond, which makes the modified binder show higher stability when facing chemical environments such as electrolytes. In addition, since three alkoxy groups are connected to the silicon atom connected to the carbon atom, this structure makes the molecular chain more stable and not easy to rotate, thereby further enhancing the chemical stability and structural strength of the formed negative electrode binder.

[0134] In some examples of the present application, the mass ratio of the hydroxydopamine monomer to the vinylsiloxane monomer is 1.5-6:1.

[0135] In the raw materials for synthesizing the negative electrode binder, two modifiers are used: hydroxydopamine monomer and vinylsiloxane monomer, and the mass fraction ratio of the hydroxydopamine monomer to the vinylsiloxane monomer is controlled at, for example, 1.5 to 6:1.

[0136] Hydroxydopamine monomers, with their unique ortho-diphenolic hydroxyl structure, provide strong adhesion. When the mass ratio of hydroxydopamine monomers to vinyl siloxane monomers is controlled within the range of 1.5 to 6:1, the adhesion performance of hydroxydopamine can be fully exerted, while other properties will not be reduced due to excessive content.

[0137] The introduction of vinyl siloxane monomers enhances the chemical stability of the negative electrode binder through Si-O bonds. Within the above ratio range (i.e., the above 1.5-6:1), the content of vinyl siloxane monomers is sufficient to provide a stable Si-O bond structure, but not too much, thereby avoiding possible negative effects, such as increased material costs or reduced processing performance.

[0138] The technical solution provided in the embodiment of the present application, the structure of three alkoxy groups connected to the silicon atom connected to the carbon atom plays a key role in the vinyl siloxane monomer, increasing the stability of the molecular chain, making it difficult to rotate, thereby enhancing the tensile strength and structural strength of the material. The appropriate content of the vinyl siloxane monomer helps to fully display this structure and improve the overall performance of the negative electrode binder.

[0139] According to the example provided in this application, the mass ratio of the hydroxydopamine monomer to the vinyl siloxane monomer is 1.5 to 6:1. Within this ratio range, the content of the vinyl siloxane monomer is sufficient to give the negative electrode binder excellent aging resistance, high and low temperature resistance and solvent resistance. The improvement of these properties helps the battery maintain stable performance in complex environments and prolongs the service life of the battery.

[0140] Preferably, the mass ratio of the hydroxydopamine monomer to the vinylsiloxane monomer is 1.8 to 3:1. This can further improve the adhesion and chemical stability of the negative electrode binder. Specifically:

[0141] Within the optimized ratio range of 1.8 to 3:1, the o-diphenol hydroxyl structure of hydroxydopamine can more effectively exert its adhesion force to ensure a firm connection between the negative electrode active material and the negative electrode current collector.

[0142] Within the optimized ratio range of 1.8 to 3:1, the amount of vinylsiloxane monomers introduced is more finely controlled, making the number and distribution of Si-O bonds more uniform, thereby further improving the chemical stability of the formed negative electrode binder. This precise regulation helps ensure that the negative electrode binder can maintain stable performance in various chemical environments. In addition, the appropriate content of vinylsiloxane monomers not only ensures that the structure of three alkoxy groups connected to the silicon atom connected to the carbon atom is fully displayed, but also makes this structure more evenly distributed in the negative electrode binder. This uniform distribution helps to improve the tensile strength and structural strength, allowing the negative electrode binder to withstand greater external forces without being easily broken.

[0143] Moreover, within the optimized ratio range of 1.8 to 3:1, the content of vinyl siloxane monomers is more precisely controlled, thus ensuring that the negative electrode binder formed has better aging resistance, high and low temperature resistance and solvent resistance. These significant improvements in performance help improve the adaptability and reliability of batteries in various complex environments.

[0144] By further accurately controlling the mass fraction ratio of the hydroxydopamine and the vinylsiloxane monomer, the preferred solution provided in the example of the present application achieves a balance of comprehensive performance while improving various performance indicators. This balance enables the negative electrode binder to have good stability and reliability while maintaining high performance, which provides strong support for the preparation of high-performance negative electrode sheets.

[0145] In some examples of the present application, the acrylic monomer and the hydroxydopamine monomer are mixed and reacted to obtain a reactant, including:

[0146] The acrylic monomer and the hydroxydopamine monomer are mixed and reacted at 50° C. to 70° C. for 1 h to 2 h.

[0147] According to this example of the present application, acrylic monomers (such as acrylic acid and / or methacrylic acid, etc.) are mixed and reacted with hydroxydopamine monomers. Specifically, the entire reaction temperature condition is 50°C to 70°C. This temperature range is selected to ensure that the reaction can proceed at a faster rate while avoiding unnecessary side reactions or decomposition of the monomers caused by excessively high temperatures. In addition, the reaction time condition is 1h to 2h. The choice of reaction time is to ensure that the reaction is fully carried out to achieve the desired degree of polymerization. Too short a time may result in incomplete reaction, while too long a time may increase energy consumption and may cause unnecessary side reactions.

[0148] Under the selected reaction temperature and time conditions, the mixed reaction of acrylic monomers and hydroxydopamine monomers can be carried out efficiently, ensuring the sufficiency of the reaction and the uniformity of the product.

[0149] Furthermore, by precisely controlling the reaction conditions, polymers with specific properties can be obtained. For example, the combination of acrylic monomers and hydroxydopamine monomers may give the polymer unique adhesion and biocompatibility. In addition, selecting appropriate reaction conditions can reduce energy consumption and production costs. At the same time, avoiding excessively high temperatures can reduce unnecessary side reactions and is beneficial to the environment.

[0150] In some examples of the present application, the step of adding a long-chain alkyl (meth) acrylate monomer and a vinyl siloxane monomer to the reactant, and then performing a polymerization reaction in the presence of a surfactant and an initiator to obtain a negative electrode binder includes the following steps S1 to S3:

[0151] Step S1, adding the long-chain alkyl (meth) acrylate monomer and the surfactant to the reactant obtained after the acrylic monomer and the hydroxydopamine monomer are mixed and reacted, and adding deionized water to prepare a pre-emulsion;

[0152] Step S2, adding the initiator to the pre-emulsion, introducing nitrogen as a protective gas, raising the temperature to 75° C. to 85° C. and then maintaining the temperature, then adding the vinyl siloxane monomer and continuing to maintain the temperature at 75° C. to 85° C. to obtain an emulsion; wherein the total time of the second insulation is 1 to 3 hours;

[0153] Step S3, filtering and drying the emulsion to obtain the negative electrode binder.

[0154] According to the above-mentioned steps S1 to S3, the polymerization reaction process for preparing the negative electrode binder is described, which includes mixing with long-chain alkyl (meth) acrylate monomers and vinyl siloxane monomers, preparation of pre-emulsion, addition of initiator, polymerization reaction under nitrogen protection, and subsequent emulsion treatment and drying steps.

[0155] Regarding step S1, i.e., the preparation of the pre-emulsion, specifically, a long-chain alkyl (meth)acrylate monomer and a surfactant are added to the reactants of the acrylic monomer and the hydroxydopamine monomer that have been mixed and reacted, and then deionized water is added to prepare the pre-emulsion.

[0156] By adding long-chain alkyl (meth) acrylate monomers, the polymer material can be given better softness, hydrophobicity and lubricity, which is crucial for the application of negative electrode binders in batteries.

[0157] The addition of surfactants can improve the dispersibility of monomers in water, help form a stable pre-emulsion, and provide a good foundation for subsequent polymerization reactions.

[0158] Regarding step S2: polymerization reaction. Specifically, add an initiator to the pre-emulsion, and heat it to 75°C to 85°C under nitrogen protection for a period of time (e.g., 1 hour). During the heat preservation process, add vinyl siloxane monomers and continue to heat (e.g., the temperature is 75°C to 85°C, i.e., the initiation temperature) for a period of time (e.g., 0.5 hours).

[0159] The addition of initiators can trigger polymerization reactions, allowing chemical bonding between monomers to form polymer chains. Nitrogen as a protective gas can prevent oxygen in the air from adversely affecting the polymerization reaction, such as inhibiting the formation of free radicals or causing oxidation of the polymer. Insulation within a specific temperature range can ensure that the polymerization reaction proceeds at a faster rate while avoiding side reactions caused by excessively high temperatures. The addition of vinyl siloxane monomers can introduce siloxane groups, enhance the adhesion and weather resistance of the polymer, and have a positive impact on the application of negative electrode binders in batteries.

[0160] Regarding step S3: that is, post-treatment of the emulsion, specifically, the emulsion obtained by the polymerization reaction is filtered and dried to obtain the negative electrode binder.

[0161] Suction filtration can remove water and unreacted monomers from the emulsion to obtain a pure polymer emulsion. The drying step can remove water from the emulsion to obtain a solid negative electrode binder. Through this step, a negative electrode binder with specific properties and morphology can be obtained to meet the requirements of battery production.

[0162] In general, this preparation process can prepare negative electrode binders with excellent performance and stability through precise step control and condition optimization, which is of great significance for improving the performance and stability of batteries.

[0163] By adopting the preparation method of the negative electrode binder provided in the embodiment of the present application, it can be ensured that the prepared negative electrode binder has a stable composition and excellent performance. The preparation method ensures uniform mixing and efficient reaction of each component in the polymerization reaction through precise step control and condition optimization, thereby obtaining a negative electrode binder with excellent performance.

[0164] The negative electrode binder provided in the embodiment of the present application has the following properties:

[0165] Adhesion: Since acrylic monomers and hydroxydopamine monomers are introduced into the polymerization reaction, the negative electrode binder finally prepared has excellent adhesion.

[0166] Flexibility: The addition of long-chain alkyl (meth) acrylate monomers gives the negative electrode binder good flexibility, enabling it to adapt to the volume changes of the battery during the charging and discharging process, reducing the risk of battery failure caused by material expansion or contraction.

[0167] Weather resistance: The introduction of vinyl siloxane monomers enhances the weather resistance of the negative electrode binder, enabling it to maintain stable performance under different environmental conditions and extend the service life of the battery.

[0168] According to the fourth embodiment of the present application, a negative electrode sheet is provided, which includes a negative electrode collector and a negative electrode active material layer arranged on at least one surface of the negative electrode collector, the negative electrode active material layer includes a negative electrode active material and a conductive agent; the negative electrode active material layer is bonded to the negative electrode collector through a binder; wherein the binder adopts the negative electrode binder composition or the negative electrode binder as described above.

[0169] The negative electrode sheet provided in the embodiment of the present application mainly consists of a negative electrode current collector and a negative electrode active material layer arranged on at least one surface of the negative electrode current collector. The negative electrode active material layer contains a negative electrode active material and a conductive agent, and is firmly bonded to the negative electrode current collector through a specific binder, which is the negative electrode binder provided in the embodiment of the present application.

[0170] The negative electrode current collector is an important component of the negative electrode of the battery, which is responsible for collecting and conducting current. The negative electrode current collector material includes metals or alloys such as copper and nickel.

[0171] Negative electrode active material: This is the main material in the negative electrode of the battery used to store and release charge. Negative electrode active materials include graphite, silicon-based materials, etc.

[0172] Conductive agent: The function of the conductive agent is to improve the conductivity of the negative electrode active material layer, ensure that the current can pass smoothly, and reduce polarization. Conductive agents include carbon black, carbon nanotubes, etc.

[0173] Negative electrode binder: The bonding between the negative electrode active material layer and the negative electrode current collector is achieved by the negative electrode binder provided in the embodiment of the present application. This negative electrode binder not only has excellent adhesion properties, which can ensure a firm connection between the negative electrode active material layer and the negative electrode current collector, but also has good electrochemical stability and mechanical strength, and can maintain a stable structure and performance during the battery charging and discharging process.

[0174] The embodiment of the present application provides a negative electrode sheet based on a specific negative electrode binder, which can significantly improve the performance and stability of the battery by optimizing the bonding method and material selection between the negative electrode active material layer and the negative electrode current collector.

[0175] According to a fifth embodiment of the present application, a battery cell is provided, the battery cell comprising: a positive electrode sheet, a negative electrode sheet and a separator; wherein the negative electrode sheet is the negative electrode sheet as described above.

[0176] According to an embodiment of the present application, a structure of a battery cell is described, which is mainly composed of a positive electrode sheet, a negative electrode sheet and a separator. The negative electrode sheet here specifically refers to the negative electrode sheet using a specific negative electrode binder described previously in this application. This battery cell design makes full use of the optimized negative electrode sheet to improve the overall performance of the battery cell.

[0177] Since the negative electrode sheet adopts the negative electrode binder provided in the embodiment of the present application, the optimization of the negative electrode binder ensures a firm connection between the negative electrode active material layer and the negative electrode current collector, reduces the interface resistance, and thus improves the charging and discharging efficiency and energy utilization of the battery cell. In addition, the optimized negative electrode sheet is also improved in mechanical strength and chemical stability, which helps to reduce the failure risk of the battery cell during the charging and discharging process and improve the safety of the battery.

[0178] The battery cell provided in the embodiments of the present application can adapt to different working environments and charging and discharging conditions, such as high temperature, low temperature, etc., and exhibits strong stability and reliability.

[0179] According to a sixth embodiment of the present application, a battery is provided, comprising a housing, a battery cell and an electrolyte; wherein the battery cell is the battery cell as described above.

[0180] According to an embodiment of the present application, a battery structure is described, which is composed of a housing, a battery cell and an electrolyte. The battery cell is a battery cell containing a specific negative electrode sheet as described previously in the present application. This battery design is intended to provide a safer and higher performance energy storage solution.

[0181] The embodiments of the present application are described in detail below in conjunction with specific embodiments.

[0182] Example 1

[0183] (1) The preparation method of the negative electrode binder is as follows:

[0184] In a 500 mL flask equipped with a glass tube, a reflux condenser, a stirrer, and a thermometer, 50 parts by mass of acrylic acid and 90 parts by mass of hydroxydopamine monomer were mixed and reacted at 60° C. for 1 hour;

[0185] 30 parts by mass of 2-ethylhexyl acrylate (a long-chain alkyl (meth) acrylate monomer) was added as a monomer into the above reaction container (500 mL flask) together with a surfactant, and then deionized water was added to prepare a pre-emulsion;

[0186] Then, an initiator was added, and nitrogen was introduced as a protective gas, and the temperature was heated to 80° C. and kept warm for 1 hour. Then, 40 parts by weight of vinyl trimethoxysilane (vinyl siloxane monomer) was added and kept warm at 80° C. (initiation temperature) for 0.5 hour to obtain a white emulsion with a blue glow;

[0187] Finally, after suction filtration and vacuum drying at 60° C., a white powder product can be obtained, which is the negative electrode binder.

[0188] (2) The specific process of preparing the negative electrode sheet is as follows:

[0189] First, the white powder product prepared above, i.e., the negative electrode binder, was dissolved in 50 wt % deionized water according to the slurry solid content of 0.8 wt % to form an aqueous dispersion;

[0190] Next, 0.5 wt% conductive carbon black Super P was added and stirred and dispersed for 1 h at a speed of 1200 rpm;

[0191] Add ammonia water to adjust the pH to 7-7.5 and continue stirring and dispersing;

[0192] Add 0.7wt% hydroxymethyl cellulose CMC and continue to stir and disperse;

[0193] Add 48 wt% graphite and continue stirring for 3 h at a speed of 1000-1500 rpm;

[0194] Place the clean copper foil (current collector) on the automatic coating machine, put on an I-shaped scraper, turn on the vacuum pump, use dust-free paper to flatten the copper foil, adjust the speed of the coating machine to 15mm / s, place the stirred slurry evenly in front of the scraper, start the coating operation, and obtain the electrode coated with slurry;

[0195] The obtained electrode is transferred to a cardboard (or other flat plate), and then placed together in a 60°C forced air drying oven, and the door is closed for drying for 15 to 30 minutes;

[0196] The baked electrode sheet is rolled and cut in sequence to prepare a negative electrode sheet;

[0197] Take a part of the negative electrode sheet and immerse it in the electrolyte, then put it in a 60℃ oven for 24 hours to dry;

[0198] Cell winding: The electrodes are stacked together in the order of positive electrode-diaphragm-negative electrode, and then rolled into a cell by automatic winding equipment. After the finished electrode has gone through steps such as packaging, liquid injection, formation, and aging, the next electrochemical performance test can be carried out.

[0199] Example 2

[0200] This embodiment 2 is basically the same as embodiment 1, except that in the preparation of the negative electrode binder, the mass fraction of the hydroxydopamine monomer is adjusted from 90 parts to 160 parts, and the other parts remain unchanged. That is, compared with embodiment 1, embodiment 2 only increases the amount of the hydroxydopamine monomer.

[0201] Example 3

[0202] This embodiment 3 is basically the same as embodiment 1, and the difference between the two is that in the preparation of the negative electrode binder, the mass fraction of the hydroxydopamine monomer is adjusted from 90 parts to 30 parts, and the others remain unchanged. That is to say, compared with embodiment 1, the amount of hydroxydopamine monomer used in embodiment 3 is greatly reduced, and the mass fraction of hydroxydopamine monomer is lower than the standard lower limit of 90 parts, which will reduce the viscosity, peeling force and other properties of the negative electrode binder to a certain extent, as shown in the subsequent Table 1.

[0203] Example 4

[0204] This embodiment 4 is basically the same as embodiment 1, and the difference between the two is that in the preparation of the negative electrode binder, the mass fraction of the hydroxydopamine monomer is adjusted from 90 parts to 120 parts, and the others remain unchanged. That is to say, compared with embodiment 1, the amount of hydroxydopamine monomer is increased in embodiment 4. It should be noted that the amount of hydroxydopamine monomer in this embodiment 4 is more preferred, so it has a good effect on the viscosity and peeling force of the negative electrode binder, which can be seen in the subsequent Table 1.

[0205] Example 5

[0206] This Example 5 is basically the same as Example 1, except that in the preparation of the negative electrode binder, the mass fraction of vinyl trimethoxy silane is adjusted from 40 parts to 80 parts, and the others remain unchanged. That is to say, compared with Example 1, the amount of vinyl trimethoxy silane used in Example 5 is increased, and the mass fraction of vinyl trimethoxy silane is higher than the standard upper limit of 60 parts, which will reduce the viscosity, peeling force and other properties of the final negative electrode binder to a certain extent, as shown in the subsequent Table 1.

[0207] Example 6

[0208] This Example 6 is basically the same as Example 1, except that in the preparation of the negative electrode binder, the mass fraction of vinyl trimethoxy silane is adjusted from 40 parts to 10 parts, and the others remain unchanged. That is, compared with Example 1, the amount of vinyl trimethoxy silane used in Example 6 is reduced, and the mass fraction of vinyl trimethoxy silane is lower than the standard lower limit of 30 parts, which will reduce the viscosity, peeling force and other properties of the final negative electrode binder to a certain extent, as shown in the subsequent Table 1.

[0209] Example 7

[0210] This embodiment 7 is basically the same as embodiment 1, and the difference between the two is that in the preparation of the negative electrode binder, the mass fraction of vinyl trimethoxy silane is adjusted from 40 parts to 60 parts, and the others remain unchanged. That is to say, compared with embodiment 1, the amount of vinyl trimethoxy silane is increased in embodiment 7, and the mass fraction of vinyl trimethoxy silane is more reasonable (within the specified range of 30 to 60 parts), compared with embodiments 5 and 6, the viscosity, peeling force and other properties of the negative electrode binder will be improved to a certain extent, as shown in the subsequent Table 1.

[0211] Example 8

[0212] This Example 8 is basically the same as Example 1, except that in the preparation of the negative electrode binder, the mass fraction of vinyl trimethoxy silane is adjusted from 40 parts to 30 parts, and the others remain unchanged. That is to say, compared with Example 1, the amount of vinyl trimethoxy silane is reduced in Example 8, but since the mass fraction of vinyl trimethoxy silane is relatively reasonable (within the specified range of 30 to 60 parts), compared with Examples 5 and 6, the viscosity, peeling force and other properties of the negative electrode binder will be improved to a certain extent, as shown in the subsequent Table 1.

[0213] Example 9

[0214] This embodiment 9 is basically the same as embodiment 1, except that in the preparation of the negative electrode binder, 2-ethylhexyl acrylate is replaced with lauryl methacrylate. That is, the long-chain alkyl (meth)acrylate monomer in embodiment 9 is different from that in embodiment 1.

[0215] Example 10

[0216] This embodiment 10 is basically the same as embodiment 1, except that in the preparation of the negative electrode binder, acrylic acid is replaced by methacrylic acid. In other words, the acrylic acid monomer in embodiment 10 is of a different type from the acrylic acid monomer in embodiment 1.

[0217] Comparative Example 1

[0218] Control Example 1 is substantially the same as Example 1, except that no hydroxydopamine monomer is added during the reaction.

[0219] Comparative Example 2

[0220] Control Example 2 is substantially the same as Example 1, except that no vinyl siloxane monomer is added during the reaction.

[0221] It should be noted that the performance of the negative electrode binders obtained in the above-mentioned Examples 1 to 10, and Comparative Examples 1 and 2 can be found in the subsequent Table 1.

[0222] The test methods and results of Examples 1 to 10 and Comparative Examples 1 and 2 are as follows:

[0223] (1) Peel strength test: GB / T2791-1995 is used to test the peel strength of the negative electrode sheet.

[0224] (2) Viscosity test: GB / T2794-2013 is used to test viscosity.

[0225] (3) Capacity retention rate test, the charge and discharge rate is 1C, after using a small current to activate the battery, the average of the first three discharge capacities is taken as the initial capacity, and the discharge capacity after 200 cycles is taken as the capacity after the cycle. Capacity retention rate = capacity after the cycle / initial capacity * 100%

[0226] Through the viscosity and peel strength tests of Examples 1 to 4 and Control Example 1, it can be seen that the addition of hydroxydopamine monomer has a significant effect on the viscosity of the polymer and the peel strength of the negative electrode slurry. The more hydroxydopamine monomer is used, the greater the peel strength.

[0227] It can be seen from the capacity retention rates after cycles of Examples 1 to 4 and Control Example 1 that when the amount of hydroxydopamine monomer used is 90 to 120 parts by mass, its effect on the bonding force and internal resistance of the negative electrode active material is in the best state. The possible reason is that although the hydroxydopamine monomer can improve the bonding force between the negative electrode current collector and the negative electrode active material and between the negative electrode materials, the hydroxydopamine monomer may increase the internal resistance, which is not conducive to the transmission of lithium ions and electrons. Therefore, excessive use of hydroxydopamine monomer leads to increased internal resistance, and too little addition of hydroxydopamine monomer leads to decreased viscosity of the negative electrode binder and insufficient adhesion to the negative electrode active material. Taking both into consideration, it is better to select an amount of hydroxydopamine monomer of 90 to 150 parts by mass, and 90 to 120 parts by mass is the best.

[0228] Through Example 1, Example 5, Example 6, Example 7, Example 8 and Control Example 2, it can be seen by comparison that, relative to Control Example 2 in which no vinyl siloxane is added, as the amount of vinyl siloxane increases, the peel strength of the electrode sheet after being soaked in the electrolyte increases significantly, and the bonding force of the negative electrode active material to the negative electrode current collector increases significantly. The peel strength performance is Example 1≈Example 7>Example 5>Example 6>Control Example 2. At the same time, it can be seen that too much vinyl siloxane does not significantly improve the peel strength of the negative electrode sheet after being soaked in the electrolyte, but instead reduces the peel strength. The possible reason is that the addition of too much vinyl siloxane increases the structural strength of the negative electrode binder, reduces the flexibility accordingly, and becomes brittle, which ultimately reduces the performance of the peel strength of the negative electrode binder.

[0229] By comparing the capacity retention rate after the cycle through Example 1, Example 5, Example 6, Example 7, Example 8 and Control Example 2, it can be seen that the addition of vinyl siloxane has a more obvious effect on improving the capacity retention rate after the battery cycle, compared with Control Example 2 without the addition of vinyl siloxane, but too much vinyl siloxane may cause the binder to be too strong and the flexibility to be reduced, causing the negative electrode active material to become brittle. Therefore, as the charge and discharge proceed, the increase and reduction of the volume of the negative electrode active material may cause the rupture and collapse of the negative electrode, thereby reducing the capacity retention rate. Therefore, the preferred amount of vinyl siloxane added is 30 to 60 parts by mass, and the best amount is 40 to 50 parts by mass.

[0230] Table 1 below shows the test results of the slurry viscosity and peel strength of each embodiment and each comparative example.

[0231] Table 1

[0232]

[0233]

[0234] Table 2 below shows the capacity retention rate test results of each embodiment and each control example.

[0235] Table 2

[0236] Serial number Capacity retention after 200 cycles Example 1 95.5 Example 2 93.5 Example 3 93.9 Example 4 95.4 Example 5 94.8 Example 6 95.0 Example 7 94.3 Example 8 95.5 Example 9 95.5 Example 10 95.6 Comparative Example 1 93.1 Comparative Example 2 92.8

[0237] In general, according to the components and dosage of the negative electrode binder provided in the embodiments of the present application, the prepared negative electrode binder has better performance in terms of viscosity, peeling force, etc.

[0238] The above embodiments focus on the differences between the various embodiments. As long as the different optimization features between the various embodiments are not contradictory, they can be combined to form a better embodiment. Considering the simplicity of the text, they will not be repeated here.

[0239] Although some specific embodiments of the present application have been described in detail by way of example, it should be understood by those skilled in the art that the above examples are only for illustration, not for limiting the scope of the present application. It should be understood by those skilled in the art that the above embodiments may be modified without departing from the scope and spirit of the present application. The scope of the present application is defined by the appended claims.

Claims

1. A negative electrode binder composition, characterized in that: The negative electrode binder composition comprises the following components: Acrylic monomers, hydroxydopamine monomers, long-chain alkyl (meth)acrylate monomers and vinyl siloxane monomers.

2. The negative electrode binder composition according to claim 1, characterized in that The mass fractions of the acrylic monomer, the hydroxydopamine monomer, the long-chain alkyl (meth)acrylate monomer and the vinyl siloxane monomer are as follows: The acrylic monomer is 50 to 100 parts; The hydroxydopamine monomer is 90 to 180 parts; The long-chain alkyl (meth) acrylate monomer is 20 to 40 parts; The vinyl siloxane monomer is 30 to 60 parts.

3. The negative electrode binder composition according to claim 1, characterized in that: The negative electrode binder composition further includes an initiator and a surfactant; The amount of the initiator is 0.1 wt% to 1 wt% of the total mass of the acrylic monomer, the hydroxydopamine monomer, the long-chain alkyl (meth) acrylate monomer and the vinyl siloxane monomer; and / or, The amount of the surfactant used is 0.5 wt % to 1 wt % of the total weight of the acrylic monomer, the hydroxydopamine monomer, the long-chain alkyl (meth)acrylate monomer and the vinyl siloxane monomer.

4. The negative electrode binder composition according to claim 1, characterized in that The acrylic monomer includes at least one of acrylic acid and methacrylic acid; The long-chain alkyl (meth)acrylate monomer includes at least one of lauryl methacrylate, myristyl methacrylate, stearic methacrylate and 2-ethylhexyl acrylate.

5. The negative electrode binder composition according to claim 1, characterized in that: The vinyl siloxane monomer includes at least one of vinyl trimethoxy silane, vinyl triethoxy silane, vinyl triisopropoxy silane and γ-methacryloxypropyl trimethoxy silane.

6. The negative electrode binder composition according to claim 3, characterized in that: The initiator includes at least one of potassium persulfate, ammonium persulfate and sodium persulfate.

7. The negative electrode binder composition according to claim 3, characterized in that: The surfactant includes at least one of sodium dodecyl sulfate, sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, sodium dioctyl sulfosuccinate, polyoxyethylene p-nonylphenol ether and polyoxyethylene p-octylphenol ether.

8. A negative electrode binder, characterized in that The chemical structural formula of the negative electrode binder is as follows: In the formula: x, y, z represent quantity, x, y, z are positive integers, and the ratio of x, y, z is 5-10:1-2:2-4.

9. A method for preparing a negative electrode binder, characterized in that: include: The acrylic monomer and the hydroxydopamine monomer are mixed and reacted to obtain a reactant; A long-chain alkyl (meth) acrylate monomer and a vinyl siloxane monomer are added to the reactant, and then a polymerization reaction is carried out in the presence of a surfactant and an initiator to prepare a negative electrode binder.

10. The method for preparing a negative electrode binder according to claim 9, characterized in that: The mass ratio of the hydroxydopamine monomer to the vinyl siloxane monomer is 1.5-6:

1.

11. The method for preparing a negative electrode binder according to claim 9, characterized in that: The acrylic monomer and the hydroxydopamine monomer are mixed and reacted to obtain the reactants including: The acrylic monomer and the hydroxydopamine monomer are mixed and reacted at 50° C. to 70° C. for 1 h to 2 h.

12. The method for preparing a negative electrode binder according to claim 9, characterized in that: The step of adding a long-chain alkyl (meth) acrylate monomer and a vinyl siloxane monomer to the reactant, and then performing a polymerization reaction in the presence of a surfactant and an initiator to obtain a negative electrode binder comprises: Adding the long-chain alkyl (meth) acrylate monomer and the surfactant to the reactant obtained after the acrylic monomer and the hydroxydopamine monomer are mixed and reacted, and adding deionized water to prepare a pre-emulsion; Add the initiator to the pre-emulsion, introduce nitrogen as a protective gas, raise the temperature to 75°C to 85°C and then keep it warm, then add the vinyl siloxane monomer and continue to keep it warm at 75°C to 85°C to obtain an emulsion; wherein the total time of the second heat preservation is 1 to 3 hours; The emulsion is filtered and dried to obtain the negative electrode binder.

13. A negative electrode sheet, characterized in that: It includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material and a conductive agent; the negative electrode active material layer is bonded to the negative electrode current collector through a binder; Wherein, the binder is the negative electrode binder composition according to any one of claims 1 to 8 or the negative electrode binder according to claim 9.

14. A battery cell, characterized in that: include: A positive electrode sheet, a negative electrode sheet and a separator; wherein the negative electrode sheet is the negative electrode sheet as claimed in claim 13.

15. A battery, characterized in that: Including shell, battery cell and electrolyte; Wherein, the battery cell is the battery cell as claimed in claim 14.

Citation Information

Patent Citations

  • Adhesive for silicon-carbon negative electrode of lithium ion battery, and preparation and application of adhesive

    CN110364735A

  • Lithium ion battery silicon-based negative electrode binder and preparation method and application thereof

    CN111785968A

  • Polymer, binder and negative electrode comprising polymer, and preparation method of negative electrode

    CN115472834A

  • Lithium ion battery negative electrode binder, preparation method thereof and negative electrode slurry

    CN116179121A

  • High-specific-energy battery binder emulsion and preparation method thereof

    CN118085810A

Cited By

  • Preparation method of lithium ion battery negative electrode binder

    CN121759122A